Histopathological Differential Diagnosis of Meningoencephalitis in Cetaceans: Morbillivirus, Herpesvirus, Toxoplasma gondii, Brucella sp., and Nasitrema sp. - Sierra, Eva; Fernández, Antonio; Felipe-Jiménez, Idaira; Zucca, Daniele; Díaz-Delgado, Josué; Puig-Lozano, Raquel; Câmara, Nakita; Consoli, Francesco; Díaz-Santana, Pablo; Suárez-Santana, Cristian; Arbelo, Manuel (Frontiers in Veterinary Science, 2020)
Infectious and inflammatory processes are among the most common causes of central nervous system involvement in stranded cetaceans. Meningitis and encephalitis are among the leading known natural causes of death in stranded cetaceans and may be caused by a wide range of pathogens. This study describes histopathological findings in post-mortem brain tissue specimens from stranded cetaceans associated with 5 relevant infectious agents: viruses [Cetacean Morbillivirus (CeMV) and Herpesvirus (HV); n=29), bacteria (Brucella sp.; n=7), protozoa (Toxoplasma gondii; n=6) and helminths (Nasitrema sp.; n=1). Aetiological diagnosis was established by molecular methods. Histopathologic evaluations of brain samples were performed in all the cases, and additional histochemical and/or immunohistochemical stains were carried out accordingly. Compared with those produced by other types of pathogens in our study, the characteristic features of viral meningoencephalitis (CeMV and HV) included the most severe and frequent presence of malacia, intranuclear and/or intracytoplasmic inclusion bodies, neuronal necrosis and associated neuronophagia, syncytia and haemorrhages, predominantly in the cerebrum. The characteristic features of Brucella sp. meningoencephalitis included the most severe and frequent presence of meningitis, perivascular cuffing, cerebellitis, myelitis, polyradiculoneuritis, choroiditis, ventriculitis, vasculitis and fibrinoid necrosis of vessels. The characteristic features of T. gondii meningoencephalitis included lymphocytic and granulomatous encephalitis, tissue cysts, microgliosis, and oedema. In the case of Nasitrema sp. infection, lesions are all that we describe since just one animal was available. The results of this study are expected to contribute, to a large extent, to a better understanding of brain-pathogen-associated lesions in cetaceans.